A Sleep-Awake Scheme Based on CoAP for Energy-Efficiency in Internet of Things - Wenquan Jin; DoHyeun Kim (JOIV : International Journal on Informatics Visualization, 2017)
Internet Engineering Task Force (IETF) have developed Constrained Application Protocol (CoAP) to enable communication between sensor or actuator nodes in constrained environments, such as small amount of memory, and low power. IETF CoAP and HTTP are used to monitor or control environments in Internet of Things (IoT) and Machine-to-Machine (M2M). In this paper, we present a sleep-awake scheme based on CoAP for energy efficiency in Internet of Things. This scheme supports to increase energy efficiency of IoT nodes using CoAP protocol. We have slightly modified the IoT middleware to improve CoAP protocol to conserve energy in the IoT nodes. Also, the IoT middleware includes some functionality of the CoRE Resource Directory (RD) and the Message Queue (MQ) broker with IoT nodes to synchronize sleepy status.